2007
DOI: 10.1177/0165025407073541
|View full text |Cite
|
Sign up to set email alerts
|

Children's depressive symptoms and their regulation of negative affect in response to vignette depicted emotion-eliciting events

Abstract: The present study examined the relationship between sub-clinical depressive symptoms and children's anticipated cognitive and behavioral reactions to two written vignettes depicting emotion-eliciting stressors (i.e., fight with one's best friend and failure at a roller blade contest). Participants ( N = 244) ranging in age between 10 and 13 were presented each vignette and then asked to rate their anticipated utilization of each of seven emotion-regulation strategies (ERs), along with the anticipated mood enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
2
13
0
3
Order By: Relevance
“…In response to negative emotions, depressed children were more likely to choose active avoidance or negative behaviors (e.g., aggression) to manage the experience than nondepressed youth, whereas the latter were more likely to choose problem-focused and active distraction strategies than the former. These general findings have been replicated in subsequent studies [27][28][29]. Taken together, findings suggest that both anxious and depressed youth experience emotion dysregulation and deficits in emotion regulation coping.…”
Section: Emotion Regulation Copingsupporting
confidence: 53%
“…In response to negative emotions, depressed children were more likely to choose active avoidance or negative behaviors (e.g., aggression) to manage the experience than nondepressed youth, whereas the latter were more likely to choose problem-focused and active distraction strategies than the former. These general findings have been replicated in subsequent studies [27][28][29]. Taken together, findings suggest that both anxious and depressed youth experience emotion dysregulation and deficits in emotion regulation coping.…”
Section: Emotion Regulation Copingsupporting
confidence: 53%
“…Specifically, dysfunctional ER ability has been related to both depressive symptoms and disorders in cross-sectional, community samples of youth (Larson et al 1990; Nolen-Hoeksema et al 1993; Reijntjes et al 2007; Silk et al 2003). While the majority of studies of ER and depressive symptoms have been cross-sectional, one longitudinal study of girls found that difficulties with ER evaluated between the ages of 5–8 years predicted depressive symptoms at age 10, suggesting that difficulties with ER predate depressive symptoms (Feng et al 2009).…”
mentioning
confidence: 99%
“…Aqui há um maior foco nas estratégias usadas e nos processos que podem ser mais ou menos eficazes, em função do contexto em causa (e.g. Carthy, Horesh, Apter, Edge, & Gross, 2010;Davis, Levine, Lench, & Quas, 2010;Dias, Vikan, & Gravås, 2000;Endrerud & Vikan, 2007;Garnefski, Rieffe, Jallesma, Terwogt, & Kraaij, 2007;Reijntjes, Stegee, Terwogt, & Hurkens, 2007;Reijntjes, Stegee, Terwogt, Kamhuis, & Telch, 2006;Saarni, 1997;Von Salisch & Vogelgesang, 2005;Zeman & Shipman, 1996, 1997.…”
Section: Construto Uni Ou Multidimensionalunclassified